MODEL PERENCANAAN PENDIDIKAN BERBASIS KARAKTER PESANTREN DALAM MEMBENTUK AKHLAKUL KARIMAH DI PONDOK PESANTREN - Bisri, Kholil; Wibowo, Tri Reza; Ainurafiq, Ainurafiq (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2024)
Character-based education in Islamic boarding schools has a very important role in shaping the noble character of students. Islamic boarding schools, as educational institutions that focus on Islamic values, strive to produce a generation with noble character who are able to face the challenges of the times. The purpose of this study is to analyze and understand the character-based education planning model in Islamic boarding schools in shaping the noble character of students. This study aims to identify the strategies and approaches used by Islamic boarding schools in designing educational programs that focus on character development. The main argument of this study is that Islamic boarding schools, as Islamic educational institutions, have a great responsibility in shaping the noble character of students through a structured character-based education planning model. The sources of informants in this study consisted of several parties who had important roles in the implementation of the character-based education planning model at the Darussalam Blok Agung Islamic Boarding School. The data collection technique in this study was qualitative, carried out through several complementary methods to obtain comprehensive information regarding the character-based education planning model at the Darussalam Blok Agung Islamic Boarding School. Data analysis in this study was carried out qualitatively by following systematic steps to interpret the information that had been collected. First, data from interviews, observations, and documents were analyzed thematically, namely by identifying themes and patterns that emerged related to the character-based education planning model at the Darussalam Blok Agung Islamic Boarding School